Secondary battery and electric device
By using combined first and second carbon-based materials in the negative electrode sheet of the secondary battery, the problem of insufficient circulation performance of the secondary battery is solved, and higher circulation performance and stability are achieved.
Patent Information
- Application Number
- CN202311643117.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The performance of existing secondary batteries has deteriorated during circulation, especially the lack of circulation performance, which is difficult to meet the needs of widespread applications.
A negative electrode sheet is adopted, including a negative current collector and an anode film layer. The negative electrode film layer is composed of a first carbon-based material (artificial graphite of secondary particles) and a second carbon-based material. The outer area of the second carbon-based material is dense and the inner area has a porous structure. By combining graphite particles of different particle sizes and roughness, the cohesion and structural stability of the electrode sheet are improved.
The circulating performance of the secondary battery is significantly improved, the expansion of the pole sheet and the occurrence of side reactions is reduced, and the stability and energy density of the battery are enhanced.
Smart Images

Figure CN119852481A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As the application scope of secondary batteries becomes wider and wider, people have higher requirements on the performance of secondary batteries, especially the cycle performance.
[0003] Therefore, how to improve the cycle performance of secondary batteries has become an urgent problem to be solved in this field. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and an object of the present application is to provide a secondary battery and an electric device, wherein the secondary battery has excellent cycle performance.
[0005] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and comprising a negative electrode active material, wherein the negative electrode active material comprises a first carbon-based material and a second carbon-based material, the first carbon-based material comprises artificial graphite of secondary particles, the second carbon-based material comprises an external region and an internal region located inside the external region, the external region refers to a region extending from the particle surface of the second carbon-based material to the inside of the particle by a distance of 2.5 μm, and in a cross-sectional view of the second carbon-based material, the total pore area of the external region is denoted as S1, the total pore area of the internal region is denoted as S2, and S2>S1.
[0006] In the present application, the negative electrode active material includes the above-mentioned first carbon-based material and the second carbon-based material. The first carbon-based material is artificial graphite secondary particles, the secondary particles have high isotropy, small expansion during the cycle, and a more stable pole piece structure, which is conducive to reducing side reactions during the cycle and helping to improve the cycle performance of the battery cell. In addition, S2>S1 of the above-mentioned second carbon-based material indicates that the structure of the outer region of the carbon-based material is denser than the inner region, and the dense surface structure is conducive to reducing the consumption of active lithium, thereby improving the cycle performance of the secondary battery.
[0007] In some embodiments, the Occhio roughness of the second carbon-based material is less than the Occhio roughness of the first carbon-based material. The Occhio roughness of the artificial graphite of the secondary particles is large, the surface has more edges and corners, and the particle size is relatively large. In addition, the Occhio roughness of the second carbon-based material is small, indicating that the surface is rounder and the particle size is relatively small. In the present application, by combining the first carbon-based material and the second carbon-based material, graphite particles of different particle sizes and different roughness are mixed together, and the prepared negative electrode pole piece can form a better particle stacking effect during cold pressing, thereby increasing the contact area between the particles, improving the bonding force, and making the negative electrode pole piece have a higher cohesive force, thereby inhibiting the pole piece expansion during the graphite ring process, and can further improve the cycle performance of the secondary battery.
[0008] In some embodiments, the Occhio roughness of the first carbon-based material is greater than or equal to 0.20, and can be selected as 0.25-0.40; and / or, the Occhio roughness of the second carbon-based material is less than or equal to 0.28, and can be selected as 0.08-0.25. By making the Occhio roughness of the first carbon-based material and the second carbon-based material respectively within the above range, the first carbon-based material particles have more edges and corners and a larger particle size, and the second carbon-based material has a more rounded surface and a smaller particle size. When the two are used in combination, it is more conducive to the negative electrode active material having a higher cohesive force, thereby inhibiting the expansion of the pole piece.
[0009] In some embodiments, the specific surface area of the first carbon-based material is 1.1 m 2 / g-2.5m 2 / g, optional 1.2m 2 / g-2.0m 2 / g; and / or, the specific surface area of the second carbon-based material is 1.0m 2 / g-2.1m 2 / g, optional 1.3m 2 / g-1.9m 2 By making the specific surface area of the first carbon-based material and the specific surface area of the second carbon-based material within the above range, the consumption of active ions in the formation of the SEI film can be reduced, which is beneficial to improving the cycle performance of the secondary battery.
[0010] In some embodiments, the gram capacity of the first carbon-based material is less than the gram capacity of the second carbon-based material. In some embodiments, the gram capacity of the first carbon-based material is 340mAh / g-360mAh / g, optionally 345mAh / g-358mAh / g; and / or, the gram capacity of the second carbon-based material is 358mAh / g-372mAh / g, optionally 365mAh / g-372mAh / g. By making the gram capacity of the first carbon-based material and the second carbon-based material within the above range, the secondary battery can have a higher volume energy density.
[0011] In some embodiments, the proportion of the artificial graphite of the secondary particles in the first carbon-based material is greater than or equal to 60%, and can be 70%-85%. By making the proportion of the artificial graphite of the secondary particles in the first carbon-based material larger, the isotropy is higher, which can effectively inhibit the expansion of the pole piece during the cycle and improve the battery cycle performance.
[0012] In some embodiments, the degree of graphitization of the first carbon-based material is less than that of the second carbon-based material. The degree of graphitization of the first carbon-based material is 90.0%-95.0%, optionally 92.0%-94.0%; and / or the degree of graphitization of the second carbon-based material is 95.0%-98.0%, optionally 95.5%-97.5%, thereby making the negative electrode have a higher gram capacity and powder compaction density.
[0013] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material. In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 8μm-18.0μm, optionally 10μm-16μm; and / or, the volume particle size Dv50 of the second carbon-based material is 10.0μm-20.0μm, optionally 12.0μm-18.0μm. As a result, the specific surface area of the carbon-based material is lower, which is conducive to the battery having a higher first coulombic efficiency.
[0014] In some embodiments, the area of the pore structure in the outer region of the second carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 ; and / or, the inner region of the second carbon-based material includes one or more areas greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of 0.15 μm 2 -2.0μm 2 By forming a structure with a dense exterior and porous interior, the first coulombic efficiency can be improved while alleviating the expansion of the electrode during the cycle and improving the stability during the cycle.
[0015] In some embodiments, 1.5≤S2 / S1≤500, and 2≤S2 / S1≤450. Thus, the cycle performance of the secondary battery can be further improved.
[0016] In some embodiments, the second carbon-based material includes primary particles. Optionally, the primary particles account for 80% or more of the second carbon-based material. This can provide a higher structural stability and reduce the occurrence of side reactions, thereby improving the cycle performance of the secondary battery.
[0017] In some embodiments, the first carbon-based material satisfies at least one of the following conditions: (1) the powder compaction density of the first carbon-based material under a pressure of 50000N is greater than or equal to 1.85g / cm 3 , optional 1.88g / cm 3 -2.00g / cm 3 ; (2) The tap density of the first carbon-based material is 0.8 g / cm 3 -1.1g / cm 3 , optional 0.85g / cm 3 -1.05g / cm 3 ; (3) [(Dv90)-(Dv10)] / (Dv50)] of the first carbon-based material is 0.8-1.5, and can be 0.9-1.4; (4) The adsorption amount of linseed oil by 100g of the first carbon-based material is 50ml-70ml, and can be 55ml-65ml. By making the first carbon-based material meet at least one of the above conditions, it is more conducive to improving the energy density, charging capacity and cycle performance of the secondary battery.
[0018] In some embodiments, the second carbon-based material satisfies at least one of the following conditions: (1) the powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80 g / cm 3 -2.10g / cm 3 , optional 1.85g / cm 3 -2.08g / cm 3 ; (2) The tap density of the second carbon-based material is 0.95 g / cm 3 -1.30g / cm 3 , optional 1.00g / cm 3 -1.25g / cm 3; (3) [(Dv90)-(Dv10)] / (Dv50)] of the second carbon-based material is 0.70-1.10, and can be optionally 0.75-1.05; (4) The volume particle size Dv90 of the second carbon-based material is 13.0μm-30.0μm, and can be optionally 16.0μm-25.0μm; (5) The adsorption amount of linseed oil by 100g of the second carbon-based material is 40mL-60mL, and can be optionally 40mL-55mL. By making the second carbon-based material meet at least one of the above conditions, it is more conducive to improving the energy density, charging capacity and cycle performance of the secondary battery.
[0019] In some embodiments, the content of the second carbon-based material in the negative electrode active material is 20wt%-80wt%, and optionally 40wt%-60wt%. By making the content of the second carbon-based material within the above range, it is more conducive to improving the cycle performance of the secondary battery.
[0020] In some embodiments, the negative electrode active material further comprises a silicon-based material. Optionally, in the negative electrode active material, the content of the silicon-based material is greater than or equal to 5 wt %, and more preferably 10 wt % to 30 wt %.
[0021] A second aspect of the present application provides an electrical device, which includes the secondary battery of the first aspect of the present application.
[0022] Effects of the Invention
[0023] The secondary battery of the present application has excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0025] Figure 1 A schematic diagram of a cross-sectional image of a particle of the second carbon-based material of the present application.
[0026] Figure 2 This is a scanning electron microscope (SEM) image of one embodiment of the first carbon-based material of the present application.
[0027] Figure 3 This is an ion polishing cross-sectional (CP) diagram of an embodiment of the second carbon-based material of the present application.
[0028] Figure 4 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0029] Figure 5 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.
[0030] Figure 6 It is a schematic diagram of an embodiment of a battery module of the present application.
[0031] Figure 7 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0032] Figure 8 yes Figure 7 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0033] Fig. 9 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0034] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate, 100 second carbon-based material, 101 external area, 102 internal area. DETAILED DESCRIPTION
[0035] Below, the embodiments of the secondary battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] At present, the application scope of secondary batteries is becoming more and more extensive, and people have higher requirements for the performance of secondary batteries. In particular, in the application of secondary batteries, the cycle performance of the battery is increasingly unable to meet the demand. Therefore, how to improve the cycle performance of secondary batteries has become an urgent problem to be solved in this field.
[0041] In view of this, a first aspect of the embodiments of the present application provides a secondary battery.
[0042] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.
[0043] [Negative electrode]
[0044] In the secondary battery of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and including a negative electrode active material, wherein the negative electrode active material includes a first carbon-based material and a second carbon-based material, the first carbon-based material includes artificial graphite of secondary particles, the second carbon-based material includes an external region and an internal region located inside the external region, the external region refers to a region extending from the particle surface of the second carbon-based material to the inside of the particle by a distance of 2.5 μm, in the cross-sectional view of the second carbon-based material, the total pore area of the external region is recorded as S1, the total pore area of the internal region is recorded as S2, and S2>S1. In the present application, "internal region" refers to the region other than the external region in the material particle.
[0045] In the present application, artificial graphite generally refers to crystalline carbon obtained by high-temperature graphitization treatment, which usually does not have a pore structure inside, or does not have a pore structure that can be directly observed from a cross-sectional image (such as a scanning electron microscope image with a magnification of 1000 times).
[0046] In the present application, the first carbon-based material comprises artificial graphite of secondary particles, the secondary particles have high isotropy, small expansion during the cycle, and a more stable pole piece structure, which is conducive to reducing side reactions during the cycle and helping to improve the cycle performance of the battery. On the other hand, S2>S1 of the second carbon-based material, that is, the number of pores in the internal region is large and / or the pore size is large, while the number of pores in the external region is small and / or the pore size is small, indicating that the structure of the external region of the carbon-based material is denser than that of the internal region, and the pore structure of the internal region can reserve the required expansion space for the change of particle volume, thereby reducing the risk of particle crushing to produce a new interface, reducing the rebound rate of the thickness of the negative electrode film layer, and thus reducing the occurrence of side reactions; the number of pores in the external region is small and / or the pore size is small, thereby making the second carbon-based material particles have a stable structure, and avoiding the electrolyte from penetrating into the pore structure inside the second carbon-based material particles as much as possible, thereby further reducing the occurrence of side reactions and reducing the consumption of active ions by SEI film formation inside the particles. Therefore, by combining the artificial graphite of the secondary particles and the second carbon-based material with S2>S1, the cycle performance of the secondary battery can be improved.
[0047] In some embodiments, the Occhio roughness of the second carbon-based material is less than the Occhio roughness of the first carbon-based material. The Occhio roughness of the artificial graphite of the secondary particles is large, and the surface has more edges and corners. In addition, the Occhio roughness of the second carbon-based material is small, indicating that the surface is rounder. In the present application, by combining the first carbon-based material and the second carbon-based material, graphite particles of different particle sizes and different roughness are mixed together, and the prepared negative electrode pole piece can form a better particle stacking effect during cold pressing, thereby increasing the contact area between the particles, improving the bonding force, and making the negative electrode pole piece have a higher cohesive force, thereby inhibiting the pole piece expansion during the graphite ring process, and can further improve the cycle performance of the secondary battery.
[0048] In some embodiments, the Ochio roughness of the first carbon-based material is greater than or equal to 0.20, for example, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, etc., or any range therebetween, preferably 0.25-0.40. The Occhio roughness of the second carbon-based material is less than or equal to 0.28, for example, it can be 0.06, 0.07, 0.08, 0.09, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.27 or any range between the two, preferably 0.08-0.25. By making the Occhio roughness of the first carbon-based material and the second carbon-based material within the above range, the surface of the first carbon-based material particles has more edges and corners and the particle size is larger, and the surface of the second carbon-based material is more rounded and the particle size is smaller. When the two are used in combination, it is more conducive to the negative electrode active material having a higher cohesion, thereby inhibiting expansion, thereby improving the cycle performance of the secondary battery.
[0049] In some embodiments, the specific surface area of the first carbon-based material is 1.1 m 2 / g-2.5m 2 / g, for example, it can be 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, etc., preferably 1.2m 2 / g-2.0m 2 / g; the specific surface area of the second carbon-based material is 1.0m 2 / g-2.1m 2 / g, for example, it can be 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, etc., preferably 1.3m 2 / g-1.9m 2 By making the specific surface areas of the first carbon-based material and the second carbon-based material within the above range, the consumption of active ions in the formation of the SEI film can be reduced, which is beneficial to improving the cycle performance of the battery.
[0050] In some embodiments, the gram capacity of the first carbon-based material is less than the gram capacity of the second carbon-based material.
[0051] In some embodiments, the gram capacity of the first carbon-based material is 340mAh / g-360mAh / g, for example, 342mAh / g, 343mAh / g, 344mAh / g, 345mAh / g, 346mAh / g, 347mAh / g, 348mAh / g, 349mAh / g, 350mAh / g, 351mAh / g, 352mAh / g, 354mAh / g, 356mAh / g, 358mAh / g, etc., preferably 345mAh / g-358mAh / g. The gram capacity of the second carbon-based material is 358mAh / g-372mAh / g, for example, 359mAh / g, 360mAh / g, 361mAh / g, 362mAh / g, 364mAh / g, 366mAh / g, 368mAh / g, 370mAh / g, 372mAh / g, etc., preferably 365mAh / g-370mAh / g. By making the gram capacity of the first carbon-based material and the second carbon-based material within the above range, the secondary battery can have a higher energy density.
[0052] In some embodiments, the amount of artificial graphite of the secondary particles in the first carbon-based material is greater than or equal to 60%, for example, it can be 62%, 65%, 68%, 70%, 72%, 74%, 76%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, etc., preferably 70%-85%. By making the amount of artificial graphite of the secondary particles account for a large proportion, the isotropy is high, which can effectively inhibit the expansion of the pole piece during the cycle and improve the battery cycle performance.
[0053] In some embodiments, the degree of graphitization of the first carbon-based material is less than the degree of graphitization of the second carbon-based material. The degree of graphitization of the first carbon-based material is 90.0%-95.0%, for example, it can be 90.5%, 91.0%, 91.5%, 92.0%, 92.5%, 93.0%, 93.5%, 94.0%, 95.0%, etc., preferably 92.0%-94.0%. The degree of graphitization of the second carbon-based material is 95.0%-98.0%, for example, it can be 95.5%, 96%, 96.5%, 97%, 97.5%, etc., preferably 95.5%-97.5%. As a result, the negative electrode material has a higher gram capacity and powder compaction density.
[0054] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material. After the first carbon-based material with a small particle size and the second carbon-based material with a large particle size are fully mixed, they can have a denser stacking effect, strengthen the particle bonding effect after cold pressing, and reduce the expansion of the pole piece. At the same time, the particle size of the second carbon-based material is within the above range, which can make the specific surface area lower, which is beneficial to improve the first coulomb efficiency of the battery. The volume distribution particle size Dv50 of the first carbon-based material is 8μm-18.0μm, for example, it can be 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, preferably 10μm-16μm. In addition, the volume particle size Dv50 of the second carbon-based material is 10.0μm-20.0μm, for example, it can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, preferably 12.0μm-18.0μm.
[0055] In some embodiments, the second carbon-based material includes at least one 2 By making the second carbon-based material include a pore structure with the above pore area, the pore structure can reserve sufficient and stable expansion space for the volume change of the second carbon-based material particles, reduce the risk of second carbon-based material particles breaking, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery.
[0056] In some embodiments, preferably, 1.5≤S2 / S1≤500, 2≤S2 / S1≤450, 2.2≤S2 / S1≤400, 2.4≤S2 / S1≤300, 2.5≤S2 / S1≤250, 2.6≤S2 / S1≤200, 2.8≤S2 / S1≤150, 3.0≤S2 / S1≤100. The inventors found in further research that when S2 / S1 is also within the above range, the secondary battery can better balance high energy density and good cycle performance.
[0057] In the present application, the total pore area S1 of the outer region and the total pore area S2 of the inner region of the second carbon-based material can be obtained by testing the cross-sectional image of the second carbon-based material. Figure 1 is a schematic diagram of a cross-sectional image of a particle of the second carbon-based material 100 of the present application. Figure 1 As shown, the region extending 2.5 μm from the particle surface of the second carbon-based material 100 to the inside of the particle is the outer region 101 , and the region inside the outer region 101 is the inner region 102 .
[0058] In the present application, the pore area, S1, and S2 values of the second carbon-based material can be obtained by using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher from Japan's JEOL company) to obtain the cross-section of the second carbon-based material; then, referring to JY / T010-1996, a scanning electron microscope (such as the Sigma300 scanning electron microscope from Germany's ZEISS company) is used to scan the cross-section of the second carbon-based material; finally, the pore area of any hole in the second carbon-based material is obtained by image processing software (such as AVIZO); as well as the total pore area S2 of the internal region and the total pore area S1 of the external region, and thereby the value of S2 / S1 is obtained. Exemplarily, samples can be obtained from different regions of the negative electrode sheet in the secondary battery, and at least 5 positions (such as 5, 10, 15 or even more) are randomly selected from the sample to obtain cross sections using a cross-section polisher, and at least 10 particles (such as 10, 20, 50 or even more particles) are randomly selected from the scanning electron microscope images of each cross section. The total pore area S2' and the total pore area S1' of the inner region of each particle cross section are obtained by image processing software according to the above definition, and the S2' / S1' value of each particle cross section is obtained. The arithmetic mean of S2' / S1' of all the measured particle cross sections is calculated as the S2 / S1 value of the second carbon-based material.
[0059] In some embodiments, the area of the pore structure in the outer region of the second carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 . The inventors also found in further research that by controlling the area of the pore structure in the outer region of the second carbon-based material within the above range, the outer region of the second carbon-based material can have a dense structure, thereby effectively improving the structural stability of the second carbon-based material and avoiding the electrolyte from penetrating into the pore structure inside the second carbon-based material particles as much as possible, thereby effectively improving the cycle performance of the secondary battery. Of course, the present application does not intend to limit the area of all pore structures in the outer region of the second carbon-based material to be less than or equal to 0.15 μm 2For example, the area of the pore structure can be controlled to be less than or equal to 0.15 μm by more than 95%, and optionally more than 99%. 2 .
[0060] In some embodiments, the inner region of the second carbon-based material includes at least one area greater than or equal to 0.25 μm 2 The inventors also found in further research that by making the internal area of the second carbon-based material include a pore structure of the above size, on the one hand, sufficient and stable expansion space can be reserved for the volume change of the second carbon-based material particles to reduce the occurrence of side reactions, and on the other hand, the compaction density of the negative electrode film layer can be increased to buffer the volume change of the negative electrode film layer.
[0061] In some embodiments, the powder compaction density of the first carbon-based material under a pressure of 50000N is greater than or equal to 1.85g / cm 3 , optional 1.88g / cm 3 -2.00g / cm 3 Therefore, a larger powder compaction density is conducive to a higher energy density of the electrode.
[0062] In some embodiments, the tap density of the first carbon-based material is 0.8 g / cm 3 -1.1g / cm 3 , optional 0.85g / cm 3 -1.05g / cm 3 Thus, the stacking effect can be improved after mixing with the second carbon-based material.
[0063] In some embodiments, the [(Dv90)-(Dv10)] / (Dv50)] of the first carbon-based material is 0.8-1.5, and can be optionally 0.9-1.4. Thus, the narrower [(Dv90)-(Dv10)] / (Dv50)] indicates that the proportion of large particles and small particles in the first carbon-based material is small, which is beneficial to the stability of electrical properties.
[0064] In some embodiments, the amount of linseed oil adsorbed by 100g of the first carbon-based material is 50ml-70ml, and optionally 55ml-65ml. Thus, by combining with the second carbon-based material, the slurry fluidity is improved.
[0065] In some embodiments, the powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80 g / cm 3 -2.10g / cm 3 , optional 1.85g / cm 3 -2.08g / cm 3 Therefore, a larger powder compaction density is conducive to the electrode having a higher energy density.
[0066] In some embodiments, the tap density of the second carbon-based material is 0.95 g / cm 3 -1.30g / cc g / cm 3 , optional 1.00g / cm 3 -1.25g / cc g / cm 3 ,Therefore, a higher tap density can improve the stacking effect of particles.
[0067] In some embodiments, [(Dv90)-(Dv10)] / (Dv50)] of the second carbon-based material is 0.70-1.10, and can be 0.75-1.05. This indicates that the proportion of large particles and small particles in the second carbon-based material is relatively small, ensuring the stability of electrical properties.
[0068] In some embodiments, the volume particle size Dv90 of the second carbon-based material is 13.0 μm-30.0 μm, and can be 16.0 μm-23.0 μm. Thus, the proportion of large particles is small, ensuring the stability of electrical properties.
[0069] In some embodiments, the adsorption amount of linseed oil by 100g of the second carbon-based material is 40mL-60mL, and can be optionally 40mL-55mL. Therefore, the lower linseed oil adsorption amount indicates that the second carbon-based material has better fluidity after being made into slurry.
[0070] In some embodiments, at least part of the surface of the second carbon-based material has a coating. Optionally, the coating includes carbon. Optionally, more than 80% of the surface of the second carbon-based material is covered with a carbon coating, and further, 90%-100% of the surface of the second carbon-based material is covered with a carbon coating. In some embodiments, the carbon in the coating includes amorphous carbon and / or crystalline carbon with a degree of graphitization between 68% and 90%. Thus, by having a coating on at least part of the surface of the second carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0071] In some embodiments, the second carbon-based material includes primary particles. Optionally, the number of primary particles in the second carbon-based material is greater than or equal to 80%. For example, it can be 80%-100%, 90%-100%, or 95%-100%. By making the second carbon-based material contain primary particles in the above proportion, it can have a higher structural stability and reduce the occurrence of side reactions, thereby improving the cycle performance of the secondary battery.
[0072] In some embodiments, the content of the second carbon-based material in the negative electrode active material is 20wt%-80wt%, optionally 40wt%-60wt%; when the content of the second carbon-based material is within the above range, the secondary battery can obtain excellent cycle performance.
[0073] In some embodiments, when the negative electrode active material in the negative electrode film layer further includes a silicon-based material, the content of the silicon-based material is greater than or equal to 5wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc., preferably 10wt% to 30wt%. This can improve the kinetic performance and energy density of the secondary battery while giving the secondary battery good cycle performance.
[0074] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0075] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0076] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0077] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0078] The negative electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector. It should be noted that the parameters of the negative electrode film layer (such as compaction density, surface density, thickness, etc.) given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. When the negative electrode film layer is arranged on both sides of the negative electrode current collector, the parameters of the negative electrode film layer on either side meet the requirements of this application, which is considered to fall within the protection scope of this application.
[0079] In the present application, the negative electrode sheet may include other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode sheet also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet also includes a protective layer covering the surface of the negative electrode film layer.
[0080] In the present application, the Occhio roughness of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art, and can be tested by methods known in the art, such as being obtained by Occhio Callisto 3D software. An exemplary test method is as follows: After dispersing the graphite particles to be tested, photographing them with Occhio Callisto 3D software to obtain a high-contrast, high-definition picture to divide the specific morphology and boundaries of the graphite particles, determine the particle projection area, and define a smooth reference by checking the maximum inscribed circle of the original contour pixel contained in the contour of the corresponding pixel. Among them, an inscribed circle with a radius of 80% of the radius of the smooth reference object is continuously inscribed in the particle projection area, and the total area of the inscribed circle is defined as 80% of the reference object, and the ratio of 80% of the smooth reference object to the particle projection area is between 0-1. The larger the ratio of the two, the closer the surface morphology of the measured particle is to smoothness; taking 80% of the maximum inscribed circle radius as the reference object radius can better define and quantify the final Occhio roughness value. The Occhio roughness in this application refers to 1-(the ratio of 80% smooth reference to the projected area of the particle), which can indicate the sphericity parameter (surface roughness) of the particle material. The larger the Occhio roughness value, the higher the surface roughness of the material.
[0081] In the present application, the gram capacity of materials (such as the first carbon-based material, the second carbon-based material, the negative electrode film layer, etc.) has a well-known meaning in the art and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol / L The electrolyte was then used as a counter electrode and a polyethylene (PE) film as an isolation membrane, and the above electrolyte was assembled into a CR2430 button cell in an argon-protected glove box; the button cell was left to stand for 12 hours, and then discharged at 0.05C constant current to 0.005V at 25°C, left to stand for 10 minutes, and then discharged at 50μA constant current to 0.005V, left to stand for 10 minutes, and then discharged at 10μA constant current to 0.005V; then charged at 0.1C constant current to 2V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, etc.).
[0082] In the present application, the specific surface area of a material (e.g., a first carbon-based material, a second carbon-based material) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0083] In this application, the volume distribution particle size D10, Dv50, and Dv90 of the material (e.g., the first carbon-based material, the second carbon-based material, etc.) are well-known in the art, which respectively represent the particle size corresponding to the cumulative volume distribution percentage of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0084] In the present application, the graphitization degree of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the crystal structure of the material. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0085] In the present application, the powder compaction density of a material (e.g., the first carbon-based material, the second carbon-based material) has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (e.g., UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: Weigh 1 g of sample powder and add a bottom area of 1.327 cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.
[0086] In the present application, the tap density of a material (e.g., a first carbon-based material, a second carbon-based material) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, GB / T5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Baite BT-301, and the test parameters are as follows: vibration frequency 250 ± 15 times / minute, amplitude 3 ± 0.2 mm, vibration number 5000 times, and measuring cylinder 25 mL.
[0087] In the present application, the oil absorption value of a material (eg, the first carbon-based material, the second carbon-based material) has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, refer to GB / T3780.2-2017, weigh 20g of the dried test sample, place the weighed sample in the mixing chamber of the oil absorption meter, the mixing chamber temperature is 23°C, and cover the lid; align the oil delivery pipe of the constant-speed burette with the top of the hole in the mixing chamber cover; start the oil absorption meter, the instrument starts to run and drip linseed oil, as the oil absorption of the sample increases, the mixed material changes from a free-flowing state to a semi-plastic agglomerate, and the viscosity of the mixture continues to increase, and the viscosity is transmitted to the torque sensor system of the oil absorption meter. When the added oil makes the semi-plastic agglomerate reach the preset torque level, the oil absorption meter and the constant-speed burette are automatically closed; read the value corresponding to the maximum torque of 70% of the fitting curve, and use the formula A=(V / m)×100 to calculate the adsorption amount A of 100g of carbon material on linseed oil, V represents the volume of linseed oil consumed by the sample corresponding to the maximum torque of 70%, in ml; m is the mass of the added sample, in g.
[0088] In the present application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0089] In the present application, the quantitative ratio of secondary particles of artificial graphite in the first carbon-based material refers to: randomly selecting a test sample in the negative electrode film layer, randomly selecting multiple test areas in the test sample, using a scanning electron microscope to obtain images of the multiple test areas, and counting the ratio of the number of secondary particles of artificial graphite in each image to the total number of particles of the first carbon-based material, and the average value of the multiple statistical results is the quantitative ratio of secondary particles of artificial graphite in the first carbon-based material.
[0090] In the present application, the quantitative ratio of primary particles in the second carbon-based material refers to: randomly selecting a test sample in the negative electrode film layer, randomly selecting multiple test areas in the test sample, using a scanning electron microscope to obtain images of the multiple test areas, and counting the ratio of the number of second carbon-based materials with primary particle morphology in each image to the total number of particles of the second carbon-based material. The average value of the multiple statistical results is the quantitative ratio of primary particles in the second carbon-based material.
[0091] It should be noted that the above-mentioned various parameter tests on the negative electrode active material or the negative electrode film layer can be conducted by sampling and testing from the prepared secondary battery according to the following steps.
[0092] Discharge the secondary battery (for safety reasons, the secondary battery is generally fully discharged); disassemble the secondary battery and take out the negative electrode sheet, and soak the negative electrode sheet in dimethyl carbonate for a certain period of time (e.g., 2h-10h); then take out the negative electrode sheet and dry it at a certain temperature and time (e.g., 60°C, more than 4h), and take out the negative electrode sheet after drying. At this time, you can take samples from the dried negative electrode sheet to test the above-mentioned parameters related to the negative electrode film layer, such as the density, gram capacity, specific surface area, etc. of the negative electrode film layer.
[0093] The dried negative electrode sheet is baked at a certain temperature and time (for example, 400°C for more than 2h), and a region of the baked negative electrode sheet is selected to sample the negative electrode active material (a blade can be used to scrape the powder for sampling); the collected negative electrode active material is sieved (for example, sieved with a 200-mesh sieve), and finally a sample that can be used to test the parameters of the above-mentioned negative electrode active materials is obtained.
[0094] The first carbon-based material and the second carbon-based material can be distinguished by scanning electron microscopy (SEM) or ion polishing cross-sectional (CP) images. The first carbon-based material and the second carbon-based material can be distinguished from the images. Figure 2 This is a SEM picture of the first carbon-based material of the present application. It can be seen from the picture that the first carbon-based material is a secondary particle morphology. Figure 3 This is an ion polishing cross-section (CP) diagram of the second carbon-based material of the present application. It can be seen from the diagram that the outer region of the second carbon-based material has a dense structure, and the inner region has a relatively large number of pores.
[0095] In the present application, the first carbon-based material mentioned above can be obtained commercially.
[0096] In some embodiments, the preparation method of the above-mentioned second carbon-based material includes: step 1, providing a raw material with a plurality of pore structures; step 2, mixing the above-mentioned raw material and the filling material evenly in a predetermined proportion, and then keeping it warm at a first temperature T1 for a first time t1, and cooling to room temperature to obtain an intermediate after the end; step 3, keeping the obtained intermediate warm at a second temperature T2 for a second time t2, and obtaining the second carbon-based material after the end.
[0097] In some embodiments, in step 1, the raw material used to prepare the second carbon-based material includes natural graphite. Natural graphite generally refers to graphite formed naturally in nature, which does not need to be graphitized, and there are usually more closed-pore structures inside the natural graphite particles. Optionally, the natural graphite includes one or more of flake graphite, natural spherical graphite and microcrystalline graphite, and more optionally includes natural spherical graphite.
[0098] "Natural spherical graphite" refers to natural graphite with a spherical or quasi-spherical shape, and not all natural graphite particles are controlled to be ideal spheres. In some embodiments, natural spherical graphite with a desired particle size and morphology can be obtained by pre-treating flake graphite, and optionally, the pre-treatment includes crushing, classification, spheroidization, purification and other processes.
[0099] In some embodiments, in step 1, the volume distribution particle size Dv50 of the raw material may be 10.5.0 μm-19.5 μm.
[0100] In some embodiments, in step 1, the specific surface area of the raw material may be greater than or equal to 2.5 m 2 / g, optional 2.5m 2 / g-10.0m 2 When the specific surface area of the raw material is within the above range, it is beneficial to carry out subsequent filling treatment and obtain the second carbon-based material with the required specific surface area, and it is also beneficial for the second carbon-based material to have both high capacity and high first coulombic efficiency. In addition, it is also beneficial for the second carbon-based material to have better kinetic properties.
[0101] In some embodiments, in step 2, the softening point temperature of the filling material is 100° C.-150° C. Optionally, the softening point temperature of the filling material is 100° C.-146° C., 100° C.-142° C., 100° C.-138° C., 100° C.-134° C., 100° C.-130° C., 104° C.-146° C., 104° C.-142° C., 104° C.-138° C., 104° C.-134° C., 104° C.-130° C.
[0102] In some embodiments, in step 2, the volume distribution particle size Dv50 of the filler material is less than or equal to 6 μm, and can be 1 μm-6 μm, 1 μm-5 μm, 2 μm-5 μm, 3 μm-5 μm. This is conducive to the filler material being melted by heat and filling into the pore structure of the raw material, and is also conducive to improving the dispersion uniformity of the filler material and the raw material.
[0103] In some embodiments, in step 2, the coking value of the filler material is 15%-40%, and can be 18%-34%. In the present application, the coking value of the filler material is a well-known meaning in the art, and can be measured by instruments and methods known in the art. For example, it can be measured with reference to GB / T 8727-2008.
[0104] In some embodiments, in step 2, the filling material includes one or more of coal tar, petroleum asphalt, polymer compounds and resins, and may optionally include one or more of coal tar and petroleum asphalt.
[0105] In some embodiments, in step 2, the mass ratio of the above-mentioned filling material to the above-mentioned raw material is (11-34):100, and can be optionally (12-33):100, (12-30):100, (12-28):100, (14-25):100.
[0106] In step 2, by adjusting one or more parameters such as the type, softening point, coking value, and addition amount of the filling material within the above-mentioned range, it is helpful to adjust the number and / or pore size of pores in the outer and inner regions of the first carbon-based material within a suitable range, which is helpful to adjust the S2 / S1 of the first carbon-based material within a suitable range.
[0107] By adjusting the type, softening point, coking value, addition amount and other parameters of the filling material within the above range, the viscosity of the filling material is not high after it is heated and melted, and it maintains good fluidity. At the same time, it is not easy to adhere to the raw material particles, which can reduce the agglomeration of the raw material particles in the subsequent preparation process. This can also reduce the problems of increased surface defects of the first carbon-based material particles and increased surface active sites due to the need to add a depolymerization step.
[0108] In some embodiments, in step 2, the heating process of uniformly mixing the raw material and the filling material in a predetermined ratio and then heating the mixture to the first temperature T1 may be a staged heating process.
[0109] In some embodiments, the phased temperature increasing process includes a first temperature increasing process, a second temperature increasing process, and a third temperature increasing process.
[0110] In some embodiments, the first temperature rising process is to raise the temperature to 200° C.-250° C. and keep the temperature at this temperature for 0.5 h-3 h.
[0111] In some embodiments, the second temperature increase process is to increase the temperature to 450°C-550°C and keep the temperature at this temperature for 0h-2h. When the holding time is 0h, it means that when the temperature is increased to the range of 450°C-550°C, no holding treatment is performed, but the temperature continues to be increased to the first temperature T1.
[0112] In some embodiments, the third temperature increasing process is to increase the temperature to the first temperature T1 and keep the temperature at the first time t1.
[0113] In the staged heating process, the temperature is first raised to 200°C. Since the heating temperature is higher than the softening point of the filling material, the filling material is melted and softened by the heat. Keeping it warm for 1 hour allows it to flow and fill into the pore structure of the raw material; then the temperature is raised to 500°C. At this time, the melted and softened filling material undergoes a carbonization reaction, gradually forming a semi-coke state and turning into a viscous liquid or solid, thereby preventing the filling material from entering the entire pore structure of the raw material; finally, the temperature is raised to the first temperature. At this time, the filling material undergoes a carbonization reaction, thereby enabling the pore structure occupied by the filling material to be effectively filled.
[0114] In some embodiments, in step 2, the temperature is raised to the first temperature T1 at a rate of 1°C / min-10°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any range thereof. Optionally, the heating rate is 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, 2°C / min-5°C / min.
[0115] In some embodiments, the heating rate of the first heating process may be 1°C / min-10°C / min, and may be 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, or 2°C / min-5°C / min. In some embodiments, the heating rate of the second heating process may be 1°C / min-10°C / min, and may be 2°C / min-8°C / min. In some embodiments, the heating rate of the third heating process may be 1°C / min-10°C / min, and may be 2°C / min-8°C / min.
[0116] In some embodiments, in step 2, the first temperature T1 is 1100° C.-1400° C. For example, the first temperature T1 may be 1100° C., 1150° C., 1200° C., 1250° C., 1300° C., 1350° C., 1400° C. or any range thereof. Optionally, the first temperature T1 is 1100° C.-1400° C., 1100° C.-1350° C., 1100° C.-1350° C., 1100° C.-1300° C., 1100° C.-1250° C., 1100° C.-1200° C.
[0117] In some embodiments, in step 2, the first time t1 is 1 hour to 5 hours. For example, the first time t1 can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours or any range thereof. Optionally, the first time t1 is 2 hours to 4 hours.
[0118] In some embodiments, in step 2, the heat treatment can be carried out in a medium frequency furnace, a roller kiln, a rotary kiln, a push plate kiln, a vertical granulation kettle, a horizontal granulation kettle, a vertical reactor, a horizontal reactor or a drum furnace, etc., which can perform programmed temperature increase.
[0119] In some embodiments, in step 2, the heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.
[0120] In step 2, by adjusting one or more of the heating rate, the first temperature, the first time, the heating process, etc. within the above-mentioned range, it is helpful to adjust the number of pores and / or the pore size in the outer region and the inner region of the second carbon-based material within a suitable range, and thus it is helpful to adjust the S2 / S1 of the second carbon-based material within a suitable range.
[0121] In some embodiments, in step 3, the second temperature T2 is 1600° C.-3000° C. Optionally, the second temperature T2 is 1600° C.-2800° C., 1650° C.-2750° C., 1650° C.-2700° C., 1700° C.-2650° C., 1750° C.-2600° C., 1850° C.-2550° C., 1950° C.-2550° C., 1950° C.-2500° C.
[0122] In some embodiments, in step 3, the second time t2 is 1.5h-6h. For example, the second time t1 can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or any range thereof. Optionally, the second time t2 is 2h-5h.
[0123] In some embodiments, in step 3, the heat treatment may be performed in a medium frequency furnace, a box-type graphitization furnace, an Acheson graphitization furnace, a continuous graphitization furnace, or an inner-string graphitization furnace.
[0124] In some embodiments, in step 3, the medium frequency furnace and the continuous graphitization heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of argon and helium.
[0125] In step 3, by adjusting one or more of the second temperature and the second time within the above range, it is beneficial to adjust the content of disordered carbon in the second carbon-based material within a suitable range, which is beneficial for the second carbon-based material to have a suitable degree of graphitization, interlayer spacing, etc.
[0126] In the preparation method of the above-mentioned second carbon-based material, by adjusting one or more of the parameters of natural graphite, the parameters of the filling material, the heating rate, the first temperature, the first time, the heating process, the second temperature, the second time, etc. within the above-mentioned range, it is beneficial to adjust the S2 / S1, graphitization degree, gram capacity, particle size, specific surface area, Ochio roughness and other parameters of the second carbon-based material.
[0127] [Positive electrode]
[0128] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0129] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0130] The positive electrode film layer generally comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is generally formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0131] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.
[0132] When the secondary battery of the present application is a lithium-ion battery, the above-mentioned positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the above-mentioned lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the above-mentioned lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds.
[0133] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium-ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and one or more of its modified compounds. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.
[0134] In some embodiments, by way of example, the positive electrode active material for the lithium-ion battery may include one or more of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, and LiMnPO4.
[0135] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0136] [Electrolytes]
[0137] In some embodiments, the electrolyte is an electrolyte solution, and the electrolyte solution includes an electrolyte salt and a solvent.
[0138] The types of the above electrolyte salts are not particularly limited and can be selected according to actual needs.
[0139] When the secondary battery of the present application is a lithium ion battery, as an example, the above-mentioned electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0140] The types of the above-mentioned solvents are not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the above-mentioned solvents may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0141] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.
[0142] [Isolation film]
[0143] The present application has no particular limitation on the type of the above-mentioned isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0144] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0145] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly by a winding process or a lamination process.
[0146] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte.
[0147] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the above soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0148] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0149] In some embodiments, Figure 5 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the above opening to close the above receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the above receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0150] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0151] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0152] Figure 6 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 6 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0153] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0154] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0155] Figure 7 and Figure 8 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 7 and Figure 8 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0156] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0157] The above-mentioned electrical devices can select secondary batteries, battery modules or battery packs according to their usage requirements.
[0158] Fig. 9 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0159] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0160] Example
[0161] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0162] Preparation of the first carbon-based material
[0163] Materials 1-1
[0164] The needle coke raw material is coarsely crushed, broken and shaped, wherein the main frequency of the crushing and shaping machine is 55Hz, to obtain an intermediate 1 with a particle size of 10μm, and the intermediate 1 and asphalt (softening point 250℃) are mixed in a ratio of 100:15, and granulated in a heating device to obtain an intermediate 2 with a particle size of 15μm. The intermediate 2 is placed in a graphitization furnace and graphitized at 3000℃. After the graphitization heat treatment, it is demagnetized and sieved to obtain secondary particles of artificial graphite.
[0165] The properties of the obtained secondary particles of artificial graphite are as follows: volume distribution particle size Dv50=15.0 μm, Ochio roughness=0.30, and graphitization degree 94%.
[0166] Materials 1-2 to 1-5
[0167] The preparation method of materials 1-2 to 1-5 is similar to that of material 1-1, except that the main frequency of the crushing and shaping machine is adjusted to obtain materials 1-2 to 1-5.
[0168] Table 1
[0169] Serial number Host frequency (Hz) Occhio Roughness Materials 1-2 67 0.19 Ingredients 1-3 65 0.20 Ingredients 1-4 60 0.25 Ingredients 1-5 20 0.45
[0170] Preparation of the second carbon-based material
[0171] Materials 2-1
[0172] The flake graphite is mechanically crushed and spheroidized, wherein the number of shaping machines in the spheroidization process is 20, the particle size after spheroidization is 18μm, and then purified to obtain natural spherical graphite. The obtained natural spherical graphite is mixed with filler petroleum asphalt (softening point is 110°C) in a ratio of 100:22, and then the mixed material is placed in a continuous heating device, heated to 200°C and kept warm for 1h, and then continuously heated to 700°C and kept warm for 1h, and then cooled to room temperature after the end to obtain an intermediate. The obtained intermediate is placed in a graphitization furnace and subjected to graphitization heat treatment at 2500°C. After the end, it is demagnetized and sieved to obtain the second carbon-based material.
[0173] The properties of the obtained second carbon-based material are as follows: S2 / S1=15, volume distribution particle size Dv50=18.0 μm, Ochio roughness=0.10, and graphitization degree 96%.
[0174] The S2 / S1 of the second carbon-based material is obtained by testing using the following method.
[0175] The sample preparation binder and the second carbon-based material powder are mixed evenly and then applied to the copper foil, dried at 60°C for 30 minutes for use; 5 samples to be tested are cut into 6mm×6mm sizes at 5 different positions and pasted on the sample stage of the CP type argon ion cross-section polisher respectively; the samples are cut using a plasma beam to obtain the cross section of each sample. The test instrument can be the IB-09010CP type argon ion cross-section polisher of Japan JEOL Company.
[0176] The cross sections of each sample of the second carbon-based material are scanned using a scanning electron microscope, and a scanned image is obtained by arbitrarily selecting an area in each sample cross section. The test may refer to JY / T010-1996. The test instrument may be a Sigma 300 scanning electron microscope from the German ZEISS company.
[0177] Randomly select cross sections of 20 particles of the second carbon-based material from the scanned image. The area extending 0.25 μm from the particle surface of the second carbon-based material to the inside of the particle is recorded as the external area, and the area inside the external area is recorded as the internal area. Use image processing software to obtain the total pore area S1' of the external area of each particle cross section and the pore area S2' of the internal area of the second carbon-based material, and calculate the value of S2' / S1'; and calculate the arithmetic mean of S2' / S1' of all 20 particles as the value of S2 / S1 of the second carbon-based material. The image processing software can be AVIZO.
[0178] Materials 2-2 to 2-5
[0179] The preparation method of materials 2-2 to 2-5 is similar to that of material 2-1, except that the number of shaping machines connected during spheroidization is adjusted to obtain materials 2-2 to 2-5.
[0180] Table 2
[0181] Serial number Number of spheroidizing shaping machines Occhio Roughness Materials 2-2 22 units 0.08 Materials 2-3 15 units 0.25 Materials 2-4 13 units 0.28 Materials 2-5 10 units 0.33
[0182] Ingredients 3:
[0183] The needle coke raw material is coarsely crushed, broken and shaped to obtain an intermediate 1 with a particle size of 15 μm. The intermediate 1 is placed in a graphitization furnace and subjected to graphitization heat treatment at 3000° C. After the graphitization heat treatment, it is demagnetized and sieved to obtain primary particles of artificial graphite.
[0184] The properties of the obtained primary particles of artificial graphite are as follows: volume distribution particle size Dv50=15.0 μm, degree of graphitization 94.2%.
[0185] Example 1
[0186] Preparation of secondary batteries
[0187] The negative electrode active material (material 1-1 and material 2-1 are mixed at a mass ratio of 1:1), conductive agent carbon black (SuperP), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.4:1:1.2:1.4 to form a negative electrode slurry. The negative electrode slurry is coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0188] Lithium iron phosphate was mixed with conductive agent carbon black (Super P) and binder polyvinylidene fluoride in a weight ratio of 96:2:2, and an appropriate amount of solvent NMP was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0189] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0190] A polyethylene film is used as an isolation film, and is placed in order with the positive electrode sheet and the negative electrode sheet prepared as above, so that the isolation film is located between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then the electrode assembly is wound; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0191] Comparative Example 1
[0192] The preparation method of Comparative Example 1 is similar to that of Example 1, except that the negative electrode active material is a mixture of Material 3 and Material 2-1 in a mass ratio of 1:1.
[0193] Performance Testing
[0194] (1) Pole expansion rate
[0195] Samples were taken from the negative electrode sheets prepared in the above embodiments and comparative examples, and the thickness of the negative electrode sheets was measured by extending the cut surface with a micrometer, which was recorded as the initial thickness of the negative electrode sheets. The secondary batteries prepared in the above embodiments and comparative examples were charged to 3.65V at a constant current of 1 / 3C, and then charged to 0.05C at a constant voltage, and then disassembled, and the thickness of the negative electrode sheets was measured again, which was recorded as the full-charge thickness of the negative electrode sheets. The full-charge expansion rate of the sheet = (full-charge thickness of the negative electrode sheets - initial thickness of the negative electrode sheets) / cold-pressed thickness of the sheet × 100%.
[0196] (2) Cycle performance test of secondary batteries
[0197] At 45°C, the prepared secondary battery was charged to 3.65V (corresponding to 100% SOC) at 1C constant current, then charged to 0.05C at constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.5V (corresponding to 0% SOC) at 1C constant current, and the discharge capacity at this time was recorded, which was the discharge capacity of the first cycle. The secondary battery was subjected to cyclic charge and discharge tests according to the above method, and the discharge capacity after each cycle was recorded.
[0198] Capacity retention rate (%) of secondary battery after 1000 cycles at 45° C.=discharge capacity after 1000 cycles / discharge capacity at the first cycle×100%.
[0199] Table 3
[0200]
[0201] From the results in Table 1, it can be seen that the present application makes the negative electrode active material in the negative electrode film layer include both the first carbon-based material (artificial graphite of secondary particles) and the second carbon-based material, the pole piece expansion rate is low, and the secondary battery obtains excellent cycle performance. In contrast, in Comparative Example 1, when the artificial graphite primary particles are used in combination with the second carbon-based material, the pole piece expands greatly due to the high anisotropy of the primary particles, which will cause SEI breakage and the generation of fresh interfaces during the cycle, resulting in poor cycle performance.
[0202] Embodiment 2-5
[0203] The type of the first carbon-based material was changed as shown in Table 4. Otherwise, a secondary battery was prepared according to the same preparation method as in Example 1. Specific parameters and test results are shown in Table 4.
[0204] It should be noted that, for the convenience of comparison, the results of Example 1 are also shown in Table 4.
[0205] Table 4
[0206]
[0207] It can be seen from the results in Table 4 that the cycle performance can be further improved by making the Occhio roughness of the second carbon-based material smaller than that of the first carbon-based material and the Occhio roughness of the first carbon-based material greater than or equal to 0.20.
[0208] Embodiment 6-9
[0209] As shown in Table 5, except that the type of the second carbon-based material was changed, a secondary battery was prepared according to the same preparation method as in Example 1. Specific parameters and test results are shown in Table 5.
[0210] It should be noted that, for the sake of comparison, the results of Example 1 are also shown in Table 5.
[0211] Table 5
[0212]
[0213] From the results in Table 5, it can be seen that, by comparing Example 9 with Examples 1 and 6-8, the cycle performance can be further improved by making the Ochio roughness of the second carbon-based material smaller than the Ochio roughness of the first carbon-based material. Furthermore, by making the Ochio roughness of the second carbon-based material less than or equal to 0.28, it is beneficial to improve the cycle performance.
[0214] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and comprising a negative electrode active material, wherein: The negative electrode active material includes a first carbon-based material and a second carbon-based material; The first carbon-based material includes secondary particles of artificial graphite; The second carbon-based material includes an external region and an internal region located inside the external region, wherein the external region refers to a region extending 2.5 μm from the particle surface of the second carbon-based material to the inside of the particle, and in the cross-sectional view of the second carbon-based material, the total pore area of the external region is denoted as S1, the total pore area of the internal region is denoted as S2, and S2>S1.
2. The secondary battery according to claim 1, wherein The Occhio roughness of the second carbon-based material is smaller than the Occhio roughness of the first carbon-based material.
3. The secondary battery according to claim 1 or 2, wherein: The Ochio roughness of the first carbon-based material is greater than or equal to 0.20, and can be optionally 0.25-0.4; and / or, The Ochio roughness of the second carbon-based material is less than or equal to 0.28, and can be optionally 0.08-0.
25.
4. The secondary battery according to any one of claims 1 to 3, wherein The specific surface area of the first carbon-based material is 1.1 m 2 / g-2.5m 2 / g, optional 1.2m 2 / g-2.0m 2 / g; and / or, the specific surface area of the second carbon-based material is 1.0m 2 / g-2.1m 2 / g, optional 1.3m 2 / g-1.9m 2 / g.
5. The secondary battery according to any one of claims 1 to 4, wherein The gram capacity of the first carbon-based material is less than the gram capacity of the second carbon-based material.
6. The secondary battery according to any one of claims 1 to 5, wherein The gram capacity of the first carbon-based material is 340 mAh / g-360 mAh / g, and can be 345 mAh / g-358 mAh / g; and / or, The gram capacity of the second carbon-based material is 358 mAh / g-372 mAh / g, and can be optionally 365 mAh / g-370 mAh / g.
7. The secondary battery according to any one of claims 1 to 6, wherein The amount of the artificial graphite of the secondary particles in the first carbon-based material accounts for greater than or equal to 60%, and can be optionally 70%-85%.
8. The secondary battery according to any one of claims 1 to 7, wherein The graphitization degree of the first carbon-based material is lower than the graphitization degree of the second carbon-based material.
9. The secondary battery according to any one of claims 1 to 8, wherein The graphitization degree of the first carbon-based material is 90.0%-95.0%, and optionally 92.0%-94.0%; and / or, The graphitization degree of the second carbon-based material is 95.0%-98.0%, and can be optionally 95.5%-97.5%.
10. The secondary battery according to any one of claims 1 to 9, wherein The volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material.
11. The secondary battery according to any one of claims 1 to 10, wherein The volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-18.0 μm, and can be 10.0 μm-16.0 μm; and / or, The volume particle size Dv50 of the second carbon-based material is 10.0 μm-20.0 μm, and can be optionally 12.0 μm-18.0 μm.
12. The secondary battery according to any one of claims 1 to 11, wherein The area of the pore structure in the outer region of the second carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 and / or, The inner region of the second carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of 0.15 μm 2 -2.0μm 2 The pore structure.
13. The secondary battery according to any one of claims 1 to 12, wherein 1.5≤S2 / S1≤500, optionally, 2≤S2 / S1≤450.
14. The secondary battery according to any one of claims 1 to 13, wherein The second carbon-based material includes primary particles; optionally, the primary particles account for greater than or equal to 80% of the second carbon-based material.
15. The secondary battery according to any one of claims 1 to 14, wherein The first carbon-based material satisfies at least one of the following conditions: (1) The powder compaction density of the first carbon-based material under a pressure of 50,000 N is greater than or equal to 1.85 g / cm 3 , optional 1.88g / cm 3 -2.00g / cm 3 ; (2) The tap density of the first carbon-based material is 0.8 g / cm 3 -1.1g / cm 3 , optional 0.85g / cm 3 -1.05g / cm 3 ; (3) [(Dv90)-(Dv10)] / (Dv50)] of the first carbon-based material is 0.8-1.5, and can be 0.9-1.4; (4) The adsorption amount of linseed oil by 100g of the first carbon-based material is 50ml-70ml, and can be optionally 55ml-65ml.
16. The secondary battery according to any one of claims 1 to 15, wherein The second carbon-based material satisfies at least one of the following conditions: (1) The powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80g / cm 3 -2.10g / cm 3 , optional 1.85g / cm 3 -2.08g / cm 3 ; (2) The tap density of the second carbon-based material is 0.95 g / cm 3 -1.30g / cm 3 , optional 1.00g / cm 3 -1.25g / cm 3 ; (3) [(Dv90)-(Dv10)] / (Dv50)] of the second carbon-based material is 0.70-1.10, and can be 0.75-1.05; (4) The volume particle size Dv90 of the second carbon-based material is 13.0 μm-30.0 μm, and can be optionally 16.0 μm-25.0 μm; (5) The adsorption amount of linseed oil by 100g of the second carbon-based material is 40mL-60mL, and can be optionally 40mL-55mL.
17. The secondary battery according to any one of claims 1 to 16, wherein The mass content of the second carbon-based material in the negative electrode active material is 20wt%-80wt%, and can be optionally 40wt%-60wt%.
18. The secondary battery according to any one of claims 1 to 17, wherein The negative electrode active material further comprises a silicon-based material; optionally, in the negative electrode active material, the content of the silicon-based material is greater than or equal to 5wt%, and more optionally 10wt% to 30wt%.
19. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 18.
Citation Information
Patent Citations
Silicon composite material, preparation method thereof, negative plate and lithium ion battery
CN112885998A
Negative pole piece and application thereof
CN114464774A
Secondary battery, battery module including same, battery pack, and device
CN114902450A
Graphitized porous silicon carbon negative electrode material, preparation method thereof and lithium ion battery
CN115642233A
Secondary battery and electric device
CN116964800A